(untitled) (The Pakistan Development Review, 1991)
In developing countries the rapid growth of the public sector during the past few decades was viewed as an important means for accelerating the pace of economic growth. In most developing countries the public sector now accounts for a prominent share of total production and investment. But the contribution of the public sector to growth has been much below expectations. In many cases public enterprises require large subsidies from the government and impose a significant fiscal burden on the economy, which leads to the notion that the private sector is much more productive than the public sector. However, little empirical work has been done in this field so that the proposals that emphasize the private sector vis-a-vis the public sector rest largely on theoretical considerations. Recent work by Khan and Reinhart (1990) is an important exception. Using cross-section data for the seventies of 24 developing countries they show that the arguments favouring the private sector in adjustment programmes have empirical support. Khan and Reinhart estimate a growth model in which the effect of private and public investment on growth is separated. A comparison of the marginal productivities of the two types of investment allows them to conclude that "all in all, there does seem to be some merit in the key role assigned to private investment in the development process by supporters of market -based strategies". [Khan and Reinhart (1990), p. 25.]